2015
DOI: 10.1063/1.4927238
|View full text |Cite
|
Sign up to set email alerts
|

Complementary split ring resonator arrays for electromagnetic energy harvesting

Abstract: By virtue of their ability to resonate at a wavelength much larger than the maximum dimension, Split-Ring Resonator (SRR) cells can be densely stacked to create energy harvesting arrays having per-unit-area power efficiency higher than a single SRR cell. While the concept of using metamaterial particles for electromagnetic energy harvesting had been demonstrated in our earlier work, the overall efficiency of an SRR array in comparison to classical antenna arrays is fundamental to the viability of this technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 37 publications
0
59
0
Order By: Relevance
“…Note that we can flexibly change the working frequency band, matching the load value by changing the value of each parameter of the MS structure. When compared to the periodic dimension of the previous works, such as the SRR element, is about 1/4 operating wavelength at 5.8 GHz [7], and the G-CSRR element is about 1/3 operating wavelength at 5.55 GHz [13], and the WG-CSRR element is about 1/5 operating wavelength at 5.6 GHz [14], the proposed design in this paper is about 1/8 operating wavelength at 2.5 GHz, which is more miniaturization. Note that the proposed closed square-ring resonant ring rather than the split-ring form from existing literature is adopted in this paper.…”
Section: Design Of the Ms Energy Harvestermentioning
confidence: 99%
See 1 more Smart Citation
“…Note that we can flexibly change the working frequency band, matching the load value by changing the value of each parameter of the MS structure. When compared to the periodic dimension of the previous works, such as the SRR element, is about 1/4 operating wavelength at 5.8 GHz [7], and the G-CSRR element is about 1/3 operating wavelength at 5.55 GHz [13], and the WG-CSRR element is about 1/5 operating wavelength at 5.6 GHz [14], the proposed design in this paper is about 1/8 operating wavelength at 2.5 GHz, which is more miniaturization. Note that the proposed closed square-ring resonant ring rather than the split-ring form from existing literature is adopted in this paper.…”
Section: Design Of the Ms Energy Harvestermentioning
confidence: 99%
“…Different from the electromagnetic metamaterial absorber [4][5][6], the small split-ring resonators (SRR) were first used to collect energy in 2012 [7]. After that, some other SRRs [8][9][10], electric-inductive-capacitive (ELC) resonators [11], and ground-backed complementary split-ring (G-CSRR) resonator have also been proposed for electromagnetic energy harvesting [12,13]. The recently reported wideband ground-backed complementary split-ring (WG-CSRR) resonator structure can improve the bandwidth [14].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 It has been shown that, in contrast with a single resonator, an array of resonators with close proximity of each other can enhance the power harvesting efficiency. 16 Furthermore, it has been shown that electrically small resonators in an array form provide wider frequency bandwidth in comparison with conventional antennas. 17 capture efficiency for the incident electromagnetic wave.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, it has been shown that electrically small resonators in an array form provide wider frequency bandwidth in comparison with conventional antennas. 17 capture efficiency for the incident electromagnetic wave. 13,14 The capture efficiency as well as the AC-to-DC conversion efficiency of the receiving adapter is very important to the overall efficiency of the MPT system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation